Meningkatkan Literasi Berbahasa Indonesia Siswa Melalui Penggunaan Media CD Interaktif - Chotimah, Chotimah (Jurnal Didaktika Pendidikan Dasar, 2022)
The purpose of this research is to find out the increase in students' Indonesian literacy through the use of interactive CD media in 6th grade elementary school students. The research method is classroom action research. Collecting data using observation techniques, tests, and interviews. The results of the study show that learning using interactive CD media can increase the activity and literacy skills in Indonesian for 6th graders of Pakaan Dajah Elementary School. Indonesian language literacy skills in students have increased, we can see from the average score of students. In the initial conditions the average value was 40, in cycle I it increased to 60, and in cycle II it increased to 85. It can conclused that the application of Interactive CD media is quite significant in improve literacy skills in Indonesian for grade 6 students at SDN Pakaan Dajah.